Registration of Times of Preserving the Lowered Temperatures of Combustion Products in The Trace of the Aerosol Flow; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Vojtkov I. S. Ivan (2016, 2016)
Title screen